Análisis de las perturbaciones (Sags y Swells) de la red de distribución para mejorar la calidad de energía en el alimentador primario “D” en la subestación Chimbacalle – Quito, basado en el uso de compensadores reactivos. - Barros Gualotuña, Danny Xavier (2021)
This research work analyzes the short duration voltage variations called sag and swell present in a distribution network devices. These events cause damage to electrical equipment and electronic ones. The analysis is focused on the primary feeder line "D" at Chimbacalle - Quito substation, with the purpose to minimize these perturbations the modeling (use of software) of a type of reactive compensator was carried out that allows the voltage to be maintained at acceptable values according to the power quality regulations. For the development of the data system, the qualitative and quantitative method was used, the experimental research has allowed the use of an analytical and deductive method to the development of the work it was necessary to collect information on electrical magnitudes. The use of reactive compensators such as the SVC compensator, that allows to mitigate voltage perturbations by injection or absorption of reactive power. For the analysis, short duration voltage variation events were performed, where a sag of 0.876 p.u. was observed by increasing the load in zone 4. Then a swell of 1.217 p.u. was visualized by disconnecting the load in zone 3. Next, it was observed that the feeder has permissible levels of THD and HD according to the regulations. It was concluded by means of a SVC (static reactive power compensator) the compensation of such disturbances generated in the primary feeder line D was carried out, which allowed mitigating such disturbances, proving its effectiveness. So, the financial calculation of such reactive compensator was made for its feasibility.